Wildfire smoke exposure has significant economic impacts on California’s licensed cannabis industry - Christopher Dillis; Van Butsic; Jeffrey Vance Martin; Amanda Reiman; Genoa Starrs; Theodore E Grantham (Environmental Research Letters, 2023)
California (USA) supports the largest legal cannabis market in the world, yet faces increasing risk from wildfire. While anecdotal evidence of impacts to cannabis crops has been documented during recent extreme fire seasons, the economic losses resulting from smoke exposure and other indirect effects (e.g., ash fall, mandatory evacuations, power outages) are not well understood. We conducted an online survey of licensed cannabis farms across the state, reporting wildfire impacts on cannabis crops from 2018 through 2021. We summarized regional variation in reported cannabis crop losses, fit a hierarchical multinomial model to assess the effects of proximity to fire and smoke exposure on crops, and trained a random forest model to make impact predictions for all state-licensed outdoor cannabis farms. We found that cannabis farms experienced wildfire-related crop losses across all cannabis growing regions in 2020, but that northern regions experienced particularly high crop loss across all four study years. We also found that exposure to wildfire smoke was a stronger predictor of reported impacts than proximity to wildfire. The output of our random forest model suggested substantial impacts for the cannabis industry in 2020, with predicted crop losses between 4.54% and 21.61% statewide, and between 9.09% and 42.83% in the northernmost counties. Estimated potential economic losses in 2020 and 2021 were as high as $1.44 billion and $970.04 million, respectively—losses which themselves exceed annual values of many of California’s other agricultural commodities. Together our results indicate substantial impacts of wildfire for the California cannabis industry as a whole. We suggest that more attention be given to strategies for mitigating cannabis crop losses from wildfires, especially in light of increasing fire occurrence and severity under climate change.